(untitled) (EAAE Annual Conference Proceedings, 2023)
The disassociation between research and practice in architecture and urban design is a recognized issue, leading to an ongoing academic debate on the credibility of the field (Dovey, Pafka 2016; Alexander 2010; Carmona 2014a; Palermo 2014). The most influential text shaping the architectural practice has very limited scientific rigour and is more of a normative interpretation of subjective observations (Marshall 2012).